Scaffold Proteins in Fibrotic Diseases of Visceral Organs - Piaopiao Sun; Liliang Yang; Keqing Yu; Jing Wang; Jie Chao (Biomolecules)
Fibrosis, characterized by excessive extracellular matrix (ECM) deposition, disrupts tissue architecture and impairs organ function, ultimately leading to severe health consequences and even failure of vital organs such as the lung, heart, liver, and kidney. Despite significant advances in understanding the molecular mechanisms underlying fibrosis, effective therapeutic options remain limited. Emerging evidence highlights scaffold proteins as critical regulators in the progression of fibrosis. These multifunctional proteins serve as molecular platforms that organize and coordinate key signaling pathways—including those governing ECM remodeling, cytoskeletal organization, and cell migration—thereby integrating both profibrotic and antifibrotic signals. Their pivotal role in linking mechanotransduction, inflammatory, and developmental signals offers a unique therapeutic window, as targeted interventions (e.g., small-molecule inhibitors, peptides, biologics, and gene therapy) are emerging to modulate these pathways. This review synthesizes recent findings on scaffold protein functions across multiple organs and discusses novel therapeutic strategies to manage and potentially reverse fibrosis.